1999
DOI: 10.1090/s0002-9947-99-01884-x
|View full text |Cite
|
Sign up to set email alerts
|

A remarkable formula for counting nonintersecting lattice paths in a ladder with respect to turns

Abstract: Abstract. We prove a formula, conjectured by Conca and Herzog, for the number of all families of nonintersecting lattice paths with certain starting and end points in a region that is bounded by an upper ladder. Thus we are able to compute explicitly the Hilbert series for certain one-sided ladder determinantal rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…So the formula of 6.9 should be regarded as an "accident" while the combinatorial description of 6.8 holds more generally, for instance, for algebras defined by 1-cogenerated ideals. On the other hand Krattenthaler and Prohaska [54] were able to show that the same "accident" takes place if the paths are restricted to certain subregions called one-sided ladders. This proves a conjecture of Conca and Herzog on the Hilbert series of one-sided ladder determinantal rings; see [24].…”
Section: E(k[x ]/Imentioning
confidence: 96%
“…So the formula of 6.9 should be regarded as an "accident" while the combinatorial description of 6.8 holds more generally, for instance, for algebras defined by 1-cogenerated ideals. On the other hand Krattenthaler and Prohaska [54] were able to show that the same "accident" takes place if the paths are restricted to certain subregions called one-sided ladders. This proves a conjecture of Conca and Herzog on the Hilbert series of one-sided ladder determinantal rings; see [24].…”
Section: E(k[x ]/Imentioning
confidence: 96%
“…, t) in certain vexillary cases; e.g. see [CH94,KP99,Gho02]. Theorem B provides a new proof that Schubert varieties X w ⊆ Fℓ n in the flag manifold are Cohen-Macaulay.…”
Section: Ladder Determinantal Idealsmentioning
confidence: 99%
“…While explaining what is behind the individual steps of the above algorithm, we illustrate each of them by the running example in which A = (0, 1), S 1 = (2, 2), S 2 = (4, 3), S 3 = (2, 5), S 4 = (8, 9), S 5 = (10, 10), S 6 = (11, 11), T 1 = (4, 1), T 2 = (5, 1), T 3 = (6, 1), T 4 = (5, 2), T 5 = (5, 5), T 6 = (5, 6), T 7 = (8, 7), T 8 = (11, 9), T 9 = (13, 10), B = (12,14); see Figure 8. Clearly, there is nothing to be said about…”
Section: Sketch Of Proofmentioning
confidence: 99%
“…Abhyankar and Kulkarni [2] have shown that the Hilbert function of ladder determinantal rings coincides with the Hilbert polynomial at all nonnegative integers. For more work on ladder determinantal rings, see [4,6,7,9,13,14,15,16,20].…”
Section: Introductionmentioning
confidence: 99%